Central composite design enabled formulation development, optimization, and characterization of bosutinib monohydrate loaded lipid nanoparticles: Cytotoxicity studies - Dhananjay Panigrahi, Surya Kanta Swain, Bikash Ranjan Jena, Prasanna Parida, Pratap Kumar Sahu (Journal of Applied Pharmaceutical Science, 2025)
The current study highlighted the significance of bosutinib monohydrate (BOS) lipid nanoparticles (LNPs) using the quality by design tool. Both the cellular absorption of coumarin-6-loaded LNPs utilized in MCF-7 cells and the cytotoxic effects of LNPs loaded with BOS on the cancer cell line MCF-7 were investigated. A reproducible product with improved selective cytotoxicity in cancer cell lines was produced by the optimized formulation. For formulation optimization, a two-factor, two-level central composite design using response surface methods was included. The dependent variables were particle size (PS) in nm (Y1) and % drug entrapment efficiency (Y2), whereas the independent variables were chosen as precirol concentration (ml) (X1) and poloxamer 188 (mg) (X2). The formulation (F8) was optimized BOS-loaded LNPs among the selected independent variables, as indicated by the overlay plots from graphical optimization and desirability value 1. This formulation is appropriate for navigating the design space with model significance using statistical analysis and analysis of variance. PS, polydispersity index, zeta potential, entrapment efficiency, and scanning electron microscopy were characterized for all the prepared lipid nanoformulations. The cytotoxicity of BOS LNPs was evaluated and a drug release study was conducted in vitro. To evaluate the cellular absorption of LNPs, a cell line investigation was conducted. Even at the same concentration, the cytotoxicity analysis shows that drug-loaded nanoparticles had more cytotoxic effects than pure drugs. During the storage condition, the drug-loaded lipidic optimized formulation batch remains stable.
Keywords: Bosutinib monohydrate, lipid nanoparticles, central composite design, cellular uptake, lyophilization, cytotoxicity studies